Informative indicator of physical health and physical fitness of university students - Blavt O.Z (Kharkov National Pedagogical University, 2012)
The problem of the dynamics of physical health and physical fitness of university students during their studies were considered. The aim of research - to identify dynamics of level of physical health and physical training of students of higher educational establishment during education. The analysis of the results of medical examinations using documentary techniques: processing and systematization of medical and health records of students and third-year students. The presence of negative dynamics deterioration in their physical health and pronounced trend annual increase in the number of students assigned to special medical groups is considered. Found that the incidence among students is growing in parallel to reduce the physical health and "low" level of health of students leads to an increase in the number of students in special medical groups.